(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article mentions that Abdulla Qodiri is one of the founders of realistic prose, and his work is closely related to the process of socio-spiritual awakening of the nation, reflects the problems of the time in his works at a high level. Hajv occupies a special place in Qadiri’s work. He used the hajv not as a mere laugh, but as an enlightening and critical tool exposing the vices of society.